Inhibition of Interleukin-4 Signalling in the Treatment of Atopic Dermatitis and Allergic Asthma - Neena Philips; Mathew Samuel (Global Journal of Allergy - Peertechz Publications, 2017)
Atopic dermatitis and allergic asthma result from amplified immune response to environmental antigens, and allergic reactions from released IgE, histamine, leukotrienes and cytokines. Environmental antigens immune cells, of innate and adaptive immunity, to stimulate interleukin-4 (IL-4) mediated activation of Th2 cells and subsequent isotype switching of B cells to produce IgE antibodies, responsible for the clinical manifestation of atopic diseases. The IL-4 receptor alpha chain (IL4Rα), which mediates IL-4 signaling, is common to IL-4 and IL-13 receptors, with IL-13 being an associated cytokine in the allergic response. US Food and Drug Administration recently approved dupilumab, which blocks IL4Rα for the treatment of moderate to severe atopic dermatitis. In controlled trials, dupilumab counteracted the allergic response and the clinical symptoms of dermatitis and asthma, and dupilumab was more effective than other available treatments. The primary safety concern of dupilumab is conjunctivitis and its long-term safety, which is unknown.